The Legitimacy of Financial Hedging in Islamic Banks - Alani, Usama; Jaradat, Abdallah (The Arab Journal of Administration, 2020)
To avoid the surrounding risks of the banks from all the sides, whatever their nature were, hedging is inevitable for it. Since Islamic banks have a distinct difference from the rest of the conventional banks, it is imperative to investigate the legitimacy of the tools used by Islamic banks to avoid risks. We can formulate the problem of the study in the following question: How are the hedging instruments in Islamic banks used legitimately? The objective of the research can be explained in the legitimacy of hedging instruments, whether they are conventional or innovative Islamic instruments and the extent to which traditional instruments are adapted to the requirements of Islamic Sharia. So, the hypothesis of the research can be sustained as follows: Financial hedging instruments used in Islamic banks may contain some suspicions from the legitimate side. The research was divided into two sections, first is dealt with risk management in Islamic banking, while the second discussed the innovative methods of hedging in Islamic banks.